Tracing Digital Divides in Indonesian Islam: Ambivalences of Media and Class. Issue 1 (13th July 2021) - Slama, Martin
Abstract: The article examines questions of the digital divide from a religious perspective. It asks about the consequences of unequal access to and limitations on uses of social media among Indonesian Muslims with regard to their Islamic practice and sociality. The article concentrates on two phenomena: Islamic preachers and their affective‐cum‐economic relationship with their followers who are often organized in Islamic study groups; and online Qur'an reading groups that are frequently part of this Islamic preacher economy. Both examples point to the ambivalences that are present in Indonesia concerning economic inequality, social belonging, the uses of new media as well as the meaning of the term class as such. The article considers how these ambivalences are coming to the fore in the context of the introduction of new media and how class boundaries are renegotiated and reintroduced in Islamic online realms. From the discussion of the two examples and the ambivalences that become apparent through them, the article concludes that mediated religiosity that demands a strong presence on social media platforms is largely a middle‐class affair in Indonesia being articulated in ways that are partly reminiscent of offline class distinctions and their ambivalences.